Odpowiedzi

2010-04-16T03:07:46+02:00
Ze wzoru, który zamieściłam w załączniku
a) a7= 4+(7-1)*2= 4+12=16
a20= 4+(20-1)*4= 4+19*4=80
a43= 4+(43-1)*4= 172
a100= 4+(100-1)*4= 400

b) a7=0+(7-1)*(-3)=-18
a20=0+(20-1)*(-3)=-57
a43=0+ (43-1)*(-3)=-126
a100=0+(100-1)*(-3)=-297

c) a7=5+(7-1)*0=5
a20=5+(20-1)*0=5
a43=5+(43-1)*0=5
a100=5+(100-1)*0=5

d) a2=a1+(n-1)*r
5=a1+(2-1)*(-1)
5=a1*(-1)
a1=-5

a7=-5+(7-1)*(-1)=-1
a20=-5+(20-1)*(-1)=-24
a43=-5+(43-1)*(-1)=-47
a100=-5+(100-1)*(-1)=-104

e) a3=a1+(n-1)*r
5=a1+(3-1)*4
5=a1+8
a1=-3

a7=-3+(7-1)*4=21
a20=-3+(20-1)*4=73
a43=-3+(43-1)*4=165
a100=-3+(100-1)*4=393

f) a60=a1+(n-1)*r
60=a1+(60-1)*(-2)
60=a1-118
a1=178

a7=178+(7-1)*(-2)=166
a20=178+(20-1)*(-2)= 140
a43=178+(43-1)*(-2)= 94
a100=178+(100-1)*(-2)= -20

5 2 5